The Disaster Box Mystery as a Media for Growing Disaster Preparedness and Literacy among Junior High School Students - Dianti, Hesti Eka Nur; Febrisari, Pila; Ridho, Ahmad Aziz; Septaria, Kiki (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The focus of this research is to strengthen landslide disaster mitigation literacy in students using Mystery Box media. The ADDIE paradigm was employed in this study’s quantitative and qualitative methods. A material expert who was a teacher at SMPN 1 Sambeng, a linguist who was a professor at the UNISLA Science Education Study Program, a media expert who was 35 students at SMPN 1 Sambeng, and a disaster extension practitioner were the subjects in this study.Focusing on the paired sample t test findings, the significance of 0.000<0.005 demonstrated a significant difference between the pretest and post-test literacy of students, implying that the mystery box media was able to raise students’ literacy for landslide catastrophes. The advice for future study is that engagement with students be enhanced so that excellent communication happens, allowing the knowledge offered to be delivered to the greatest extent possible and assisting students in increasing their motivation in the realm of literacy.